UJI KANDUNGAN BAKTERI Escherichia coli PADA AIR MINUM ISI ULANG DARI DEPOT AIR MINUM ISI ULANG DI KABUPATEN REMBANG Testing of Escherichia Coli Bacteria Content in Drinking Water Refill from Drinking Water Refill Depot in Rembang Sub-district - Maulita Cut Nuria; Abdur Rosyid; Sumantri Sumantri (Universitas Wahid Hasyim, 2009)
Water refill is water that has through purification processes both Ultraviolet and ionization, by many stages of filtration to obtain clean water, in order to provide human needs. This research performed by Athena, et.al., (2003) to shows that Total Coli and Escherichia coli in high-enough amounts inside water refill from water refill depot (DAMIU) in Jakarta, Tangerang, and Bekasi. There are many efforts related with this water refill that causes DAMIU developed rapidly, so that required monitoring improvement because water is the primary needs of human being. This research aims to identify Escherichia coli bacteria content that exist in drinking water of water refill from DAMIU in Rembang Sub district. This research is survey type, equipped with microbiology test using MPN method (Most Probable Number). The populations are 25 DAMIU in Rembang sub-district. Data analysis performed descriptively. Test, conducted by water refill sampling, which produced by DAMIU in Rembang sub-district. The testing includes: approximation test using Lactosa Broth (LB) medium, confirmation test using Briliant Green Lactose Bile Broth (BGLB) medium, complementary test using Mc. Conkey medium and Gram painting was performed to identify bacteria types using microscope by 100 times magnification, and Biochemistry test that is IMVIC (Indol, Methyl-Red, Voges Proskauer, and Citrat). In water refill which produced by DAMIU in Rembang Sub district, there is 1 sample (4%) with MPN value of E. coli 13/100 ml and Coliform MPN 21/100 ml, does not fulfill the bacteriology requirements of drinking water quality, according to Health Minister Decree No.907/MENKES/SK/VII/2002 : ³The existence of E.Coli bacteria 0/100 ml sample´, while 24 samples has fulfill the requirements, with MPN value of E.Coli and Coliform < 2, so that it safe and ready to consume. Keywords: Water refill Depot (DAMIU), Most Probable Number (MPN), Escherichia coli